Foaming master batch and preparation method thereof
By using foaming masterbatches containing composite nucleating agents and heat absorbents in PET and rPET foaming materials, the problems of low melt strength and uneven bubble cells during foaming are solved, and uniform and fine bubble cells are achieved Structural and low foam density effect.
Patent Information
- Application Number
- CN202411577552.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After melting during the foaming process, the melt strength of PET and rPET is low, the cell pore size is large and uneven, and the foam density is relatively high.
Using a foaming masterbatch containing matrix resin, heat absorbent, organic foaming agent, composite nucleating agent and lubricating and dispersing agent, melt extrusion and granulation are carried out through a screw extruder, and combined with air-cooled die surface hot cut The pelleting system was performed.
A uniform and fine cell structure is achieved in PET and rPET foaming materials, which improves melt strength, reduces foaming density, and is cost-effective.
Smart Images

Figure CN119431923A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of foaming, and in particular to a foaming masterbatch and a preparation method thereof. Background Art
[0002] Foaming materials are widely used in functional application fields such as thermal insulation and energy saving, weight reduction, structural functions, impact resistance and comfort, covering multiple industries such as building materials and construction, furniture and appliances, oil and water transportation, transportation, military industry and logistics packaging. Due to its wide range of uses, the market size of foaming materials currently maintains a high growth rate of 20% per year. It is currently the fastest growing field in the application of new materials and has also attracted great attention from the industry. From the perspective of the recycling value chain, polyethylene terephthalate (PET) is the best recycled plastic category in the world due to its convenient recycling and high recycling price. In terms of downstream recycling, recycled polyethylene terephthalate (rPET) materials are mainly used for downgrading to produce recycled PET fibers.
[0003] In order to expand the recycling methods of waste PET, it is necessary to develop foaming masterbatch suitable for PET and rPET. Summary of the invention
[0004] The purpose of the present invention is to provide a foaming masterbatch and a preparation method thereof, aiming to solve the problems faced by foaming materials of PET, especially semi-crystalline materials such as rPET, in the processing process, such as low melt strength after melting, large and uneven pore diameter during foaming, and high foaming density.
[0005] To achieve one aspect of the above-mentioned invention object, the present invention adopts the following technical solution:
[0006] A foaming masterbatch comprising the following components:
[0007] (a) 100.0 parts by weight of base resin;
[0008] (b) 15.0 to 45.0 parts by weight of a heat absorbent;
[0009] (c) 10.0 to 35.0 parts by weight of an organic foaming agent;
[0010] (d) 80 to 120 parts by weight of a nucleating agent;
[0011] (e) 8.0 to 18.0 parts by weight of lubricating and dispersing agents;
[0012] Wherein, the nucleating agent is a composite nucleating agent composed of an inorganic nucleating agent, a citrate and an organic nucleating agent.
[0013] To achieve another aspect of the above-mentioned object of the invention, the present invention provides a method for preparing the above-mentioned foaming masterbatch, the preparation method comprising the following steps:
[0014] (1) adding 100.0 parts by weight of base resin, 15.0-45.0 parts by weight of heat absorbent, 10.0-35.0 parts by weight of organic foaming agent, 80-120 parts by weight of nucleating agent and 8.0-18.0 parts by weight of lubricant and dispersant into a mixer and mixing;
[0015] (2) The mixed material obtained in step (1) is melt-extruded through a screw extruder and granulated to obtain a foaming agent masterbatch material; preferably, the barrel temperature of the screw extruder is between 90 and 110° C., the transition zone temperature is between 90 and 110° C., and the head temperature is between 90 and 105° C.; preferably, the main engine speed of the screw extruder is 10 to 20 rpm.
[0016] Preferably, pelletizing is performed by an air-cooled die face hot cutting system during pelletizing.
[0017] To achieve another aspect of the above-mentioned object of the invention, the present invention also provides the use of the above-mentioned foaming masterbatch or the foaming masterbatch prepared according to the above-mentioned method in PET foamed products.
[0018] The technical solution of the present invention has at least the following beneficial effects:
[0019] (1) The composite nucleating agent is contained in the foaming masterbatch of the present invention, and the composite nucleating agent is combined with various auxiliary agents for granulation, which is helpful for the dispersion of the nucleating agent in the foaming material, thereby giving full play to the role of the nucleating agent in regulating the crystallization rate of PET and promoting the miniaturization of the grain size. The composite nucleating agent also has the function of foaming nucleation, which is helpful for forming a uniform and fine cell structure. In addition, the composite nucleating agent used in the foaming masterbatch of the present invention also has the advantage of low cost.
[0020] (2) The foaming masterbatch of the present invention contains an endothermic agent and a chemical foaming agent. During the foaming process of the PET material, the heat absorption and release are balanced, which is conducive to the formation of uniform and dense bubbles without sacrificing the excellent mechanical properties of the PET material. It is suitable for chemical foaming extrusion of PET or rPET foamed boards. The obtained foamed material has the advantages of small pore size, uniform pore distribution and lighter board.
[0021] (3) The present invention uses polyolefin and modified polyolefin resin as the base resin, and mixes them evenly with chemical foaming agent, nucleating agent, lubricant and dispersant and other additives, uses a screw extruder to extrude the material strips, and is equipped with an air-cooled die surface hot cutting system. The foaming agent is used in the form of pellets, which is beneficial to the stability of the production process and reduces dust. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 1.
[0023] Figure 2This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 2.
[0024] Figure 3 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 3.
[0025] Figure 4 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 4.
[0026] Figure 5 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 5.
[0027] Figure 6 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Example 6.
[0028] Figure 7 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 1.
[0029] Figure 8 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 2.
[0030] Fig. 9 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 3.
[0031] Fig.10 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 4.
[0032] Fig.11 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 5.
[0033] Fig.12 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 6.
[0034] Fig.13 This is a scanning electron microscope image of the PET foam material prepared from the foaming masterbatch of Comparative Example 7. DETAILED DESCRIPTION
[0035] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.
[0036] Since PET and rPET have strong melt fluidity after melting during the foaming process, and the melt strength is low and difficult to encapsulate gas, and at the same time, crystallization nucleation and foaming nucleation affect each other, resulting in large and uneven pore size and high foaming density in the foaming process.
[0037] In order to solve the above problems, the first aspect of the present invention provides a foaming masterbatch, wherein the foaming masterbatch comprises the following components:
[0038] (a) 100.0 parts by weight of base resin;
[0039] (b) 15.0 to 45.0 parts by weight of a heat absorbent;
[0040] (c) 10.0 to 35.0 parts by weight of an organic foaming agent;
[0041] (d) 80 to 120 parts by weight of a nucleating agent;
[0042] (e) 8.0 to 18.0 parts by weight of lubricating and dispersing agents;
[0043] Wherein, the nucleating agent is a composite nucleating agent composed of an inorganic nucleating agent, a citrate and an organic nucleating agent.
[0044] In some embodiments, in the nucleating agent, the weight ratio of the inorganic nucleating agent: the citrate: the organic nucleating agent is (1.5-15.0):(60.0-108.0):(9.0-15.0).
[0045] In some embodiments, the inorganic nucleating agent is selected from one or more of talc, silicon dioxide, hydrotalcite, zeolite powder, mica powder, and montmorillonite. The inorganic nucleating agent has the characteristics of high surface energy and high specific surface area, can reduce the nucleation barrier of crystallization nucleation and the nucleation barrier of foaming nucleation, and has the advantages of high nucleation efficiency and low price.
[0046] In some embodiments, the citrate is selected from one or more of trisodium citrate or tripotassium citrate.
[0047] In some preferred embodiments, the citrate is a pretreated citrate, and the pretreatment step includes: grinding and sieving the citrate to be treated to a particle size of less than 150 μm (such as 100 μm, 50 μm, 30 μm or less), and then drying at 140-160° C., such as drying for 2 h, 4 h, 8 h, etc.
[0048] In some embodiments, the organic nucleating agent is selected from one or more of a rosin-based nucleating agent and an ethylene-methacrylate nucleating agent.
[0049] The organic nucleating agent and citrate in the present invention have good compatibility with PET or rPET and are easy to disperse. In particular, the pre-treated citrate is substantially free of water, which can prevent PET from being hydrolyzed at high temperatures; and the particle size of the citrate is suitable after grinding and sieving, which is conducive to good dispersion and more uniform crystallization nucleation. Uniform crystallization can play a role similar to cross-linking, which helps to improve the melt strength of PET, thereby making the PET melt more capable of encapsulating gas and preventing cell rupture and stringing during the bubble growth stage.
[0050] In some embodiments, the endothermic agent is selected from one or more of magnesium hydroxide and aluminum hydroxide.
[0051] In some embodiments, the organic foaming agent is selected from one or more of azodicarbonamide and 5-phenyltetrazole.
[0052] In view of the high processing temperature of PET and rPET in the prior art, the local heat release caused by the decomposition of the foaming agent causes the local temperature to rise, the thermal decomposition to intensify, the melt strength to decrease, and the cell rupture and aggregation to cause aging and string holes and other problems; in the present invention, the organic foaming agent is used in combination with a heat absorber, and the heat absorber can absorb part of the heat to prevent local overheating of the melt and improve the melt strength.
[0053] In some embodiments, the matrix resin is selected from one or more of polyethylene, ethylene-octene copolymer, ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, and ethylene-methyl methacrylate copolymer. These resins have high melt strength after melting, especially copolymerized olefins and grafted modified olefins, which have good compatibility with PET and entangle with PET molecular chains in the molten state, and can also improve the melt strength of the PET melt. At the same time, using the matrix resin to wrap the foaming agent to make a foaming masterbatch can block part of the heat to delay the premature decomposition of the foaming agent.
[0054] In some embodiments, the lubricant and dispersant is selected from one or more of pentaerythritol stearate, calcium stearate, barium stearate, magnesium stearate, polyethylene wax, oxidized polyethylene wax, refined paraffin wax, and polyethylene glycol. The lubricant and dispersant is not only conducive to the molding of the masterbatch, but also can promote the uniform dispersion of other components, so that various components can fully play their role, thereby obtaining a foamed sheet with fine and uniform pores and low average foaming density.
[0055] The second aspect of the present invention provides a method for preparing the foaming masterbatch, the method comprising the following steps:
[0056] (1) adding 100.0 parts by weight of base resin, 15.0-45.0 parts by weight of heat absorbent, 10.0-35.0 parts by weight of organic foaming agent, 80-120 parts by weight of nucleating agent and 8.0-18.0 parts by weight of lubricant and dispersant into a mixer and mixing;
[0057] (2) The mixed material obtained in step (1) is melt-extruded through a screw extruder and granulated to obtain a foaming agent masterbatch material; preferably, the barrel temperature of the screw extruder is between 90 and 110° C., the transition zone temperature is between 90 and 110° C., and the head temperature is between 90 and 105° C.; preferably, the main engine speed of the screw extruder is 10 to 20 rpm.
[0058] The inventors have found that water can easily cause PET to hydrolyze at high temperatures, resulting in uneven cells and prone to cross-cell formation, so it is necessary to avoid the introduction of water as much as possible. Therefore, preferably, a system that does not use water is used as much as possible during granulation, such as pelletizing through an air-cooled die surface hot cutting system.
[0059] The screw extruder used in the method according to the present invention can be a conventional screw extruder, for example including but not limited to a conical screw extruder, a parallel screw extruder, and the like.
[0060] The third aspect of the present invention provides the use of the foaming masterbatch or the foaming masterbatch prepared according to the method in a foamed product of PET.
[0061] It should be understood that in the present invention, unless otherwise specified, the PET generally covers non-recycled and recycled PET.
[0062] Hereinafter, a foaming masterbatch according to an embodiment of the present invention will be further described in detail with reference to examples, but the present invention is not limited thereto.
[0063] <Source of raw materials>
[0064] Trisodium citrate and tripotassium citrate are commercially available raw materials.
[0065] Pretreatment of citrate: The commercially available citrate has a 100 mesh sieve rate of less than 15%. The commercially available trisodium citrate or tripotassium citrate is ground into powder, passed through a 100 mesh sieve (the particle size after sieving is less than 150 μm), and then dried at 160° C. for 2 h to obtain pretreated trisodium citrate or pretreated tripotassium citrate.
[0066] Ethylene-methacrylate nucleating agent: Surlyn-8920, The Dow Chemical Company.
[0067] The rest are commercially available materials.
[0068] <Test Method>
[0069] Gas emission: Detected using displacement method gas emission detection equipment;
[0070] Thermal decomposition temperature: detected by DSC differential scanning calorimeter;
[0071] Foam board density: density balance;
[0072] Cell image: SEM;
[0073] Screw holding force and static bending strength: Use a universal testing machine and test in accordance with GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels".
[0074] Example 1
[0075] Raw materials: 100.0 parts by weight of polyethylene resin, 35.0 parts by weight of aluminum hydroxide, 25.0 parts by weight of azodicarbonamide, 3.0 parts by weight of talc, 108.0 parts by weight of pretreated trisodium citrate, 9.0 parts by weight of ethylene-methacrylate nucleating agent, 3.2 parts by weight of calcium stearate, and 8.8 parts by weight of refined paraffin.
[0076] Preparation of foaming masterbatch:
[0077] (1) Add the above raw materials into a mixer and mix them, then immediately bag and seal them;
[0078] (2) The mixed material obtained in step (1) is melt-extruded through a single screw extruder, wherein the barrel temperature of the screw extruder is set to between 92° C. and 95° C., the transition zone temperature is 95° C., the die head temperature is 92° C., the main engine speed of the single screw extruder is 15 rpm, and an air-cooled die face hot cutting system is equipped for pelletizing.
[0079] Example 2
[0080] Raw materials: 100.0 parts by weight of ethylene-vinyl acetate copolymer, 35.0 parts by weight of aluminum hydroxide, 25.0 parts by weight of azodicarbonamide, 3.0 parts by weight of talc, 108.0 parts by weight of pretreated trisodium citrate, 9.0 parts by weight of ethylene-methacrylate nucleating agent, 3.2 parts by weight of calcium stearate, and 8.8 parts by weight of refined paraffin.
[0081] Preparation of foaming masterbatch:
[0082] (1) Add the above raw materials into a mixer and mix them, then immediately bag and seal them;
[0083] (2) The mixed material obtained in step (1) is melt-extruded through a single screw extruder, wherein the barrel temperature of the screw extruder is set to between 92° C. and 95° C., the transition zone temperature is 95° C., the die head temperature is 92° C., the main engine speed of the single screw extruder is 15 rpm, and an air-cooled die face hot cutting system is equipped for pelletizing.
[0084] Example 3
[0085] Raw materials: 100.0 parts by weight of ethylene-vinyl acetate copolymer, 20.0 parts by weight of magnesium hydroxide, 30.0 parts by weight of 5-phenyltetrazolyl, 3.0 parts by weight of hydrotalcite, 100.0 parts by weight of pretreated trisodium citrate, 9.0 parts by weight of ethylene-methacrylate nucleating agent, 3.0 parts by weight of calcium stearate, and 5.0 parts by weight of refined paraffin.
[0086] Preparation of foaming masterbatch:
[0087] (1) adding the raw materials of the foaming agent into a mixer for mixing, and immediately bagging and sealing the materials after discharging;
[0088] (2) The mixed material obtained in step (1) is melt-extruded through a single screw extruder, wherein the barrel temperature of the screw extruder is set to between 92° C. and 95° C., the transition zone temperature is 95° C., the die head temperature is 92° C., the main engine speed of the single screw extruder is 15 rpm, and an air-cooled die face hot cutting system is equipped for pelletizing.
[0089] Example 4
[0090] Raw materials: 100.0 parts by weight of ethylene-octene copolymer (ENGAGE 8003EL, Dow Chemical), 40.0 parts by weight of aluminum hydroxide, 15.0 parts by weight of azodicarbonamide, 1.5 parts by weight of hydrotalcite, 1.5 parts by weight of zeolite powder, 90.0 parts by weight of pretreated trisodium citrate, 10.0 parts by weight of sodium dehydroabietate, and 8.0 parts by weight of pentaerythritol stearate.
[0091] Preparation of foaming masterbatch:
[0092] (1) Add the above raw materials into a mixer and mix them, then immediately bag and seal them;
[0093] (2) The mixed material obtained in step (1) is melt-extruded through a parallel twin-screw extruder, wherein the barrel of the screw extruder is set between 95° C. and 98° C., the transition zone temperature is 95° C., the die head temperature is 95° C., the main engine speed of the parallel twin-screw extruder is 20 rpm, and an air-cooled die face hot cutting system is provided for pelletizing.
[0094] Example 5
[0095] Raw materials: 100.0 parts by weight of ethylene-butyl acrylate copolymer, 40.0 parts by weight of aluminum hydroxide, 35.0 parts by weight of azodicarbonamide, 15.0 parts by weight of montmorillonite, 60.0 parts by weight of pretreated trisodium citrate, 15.0 parts by weight of ethylene-methacrylate nucleating agent, 4.0 parts by weight of magnesium stearate, and 6.0 parts by weight of refined paraffin.
[0096] Preparation of foaming masterbatch:
[0097] (1) Add the above raw materials into a mixer and mix them, then immediately bag and seal them;
[0098] (2) The mixed material obtained in step (1) is melt-extruded through a conical twin-screw extruder, wherein the barrel of the screw extruder is set between 92° C. and 98° C., the transition zone temperature is 95° C., the die head temperature is 95° C., the main engine speed of the conical twin-screw extruder is 20 rpm, and an air-cooled die face hot cutting system is equipped for pelletizing.
[0099] Example 6
[0100] Raw materials: 100.0 parts by weight of ethylene-vinyl acetate copolymer, 30.0 parts by weight of aluminum hydroxide, 25.0 parts by weight of 5-phenyltetrazolyl, 1.5 parts by weight of silicon dioxide, 70.0 parts by weight of pretreated trisodium citrate, 10.0 parts by weight of sodium dehydroabietate, 5.0 parts by weight of calcium stearate, and 5.0 parts by weight of polyethylene glycol.
[0101] Preparation of foaming masterbatch:
[0102] (1) Add the above raw materials into a mixer and mix them, then immediately bag and seal them;
[0103] (2) The mixed material obtained in step (1) is melt-extruded through a conical twin-screw extruder, wherein the barrel of the screw extruder is set between 92° C. and 98° C., the transition zone temperature is 95° C., the die head temperature is 95° C., the main engine speed of the conical twin-screw extruder is 25 rpm, and an air-cooled die face hot cutting system is equipped for pelletizing.
[0104] Comparative Example 1
[0105] The process was carried out in the same manner as in Example 1, except that no endothermic aluminum hydroxide was added.
[0106] Comparative Example 2
[0107] The process is carried out in the same manner as in Example 1, except that the trisodium citrate pretreated with the citrate and the organic nucleating agent ethylene-methacrylate nucleating agent are not added, and the amount of the inorganic nucleating agent talc is 30 parts by weight.
[0108] Comparative Example 3
[0109] The same procedure as in Example 1 was followed except that no azodicarbonamide was added.
[0110] Comparative Example 4
[0111] The process is carried out in the same manner as in Example 1, except that the base resin polyethylene is not added, and the remaining materials are not granulated after being mixed evenly.
[0112] Comparative Example 5
[0113] The process was carried out in the same manner as in Example 1, except that no lubricant and dispersant calcium stearate and refined paraffin were added.
[0114] Comparative Example 6
[0115] The same method as Example 1 was used, except that the commercially available trisodium citrate was directly tested without grinding or drying.
[0116] Comparative Example 7
[0117] The same method as in Example 1 was used, except that an equal amount of aluminum hydroxide was replaced by sodium bicarbonate.
[0118] Results test:
[0119] The foaming masterbatch of each embodiment and comparative example was added to the PET recycled material to prepare a foamed board, and relevant performance tests were performed. The specific test results are shown in Table 1 below.
[0120] Preparation of foamed board:
[0121] PET recycled material: 100 parts by weight;
[0122] Pentaerythritol stearate: 1 part by weight;
[0123] Oxidized polyethylene wax: 2 parts by weight;
[0124] Heavy calcium carbonate: 100 parts by weight;
[0125] Chain extender triglycidyl isocyanurate: 1 part by weight;
[0126] Foaming regulator HL-901 for sheet materials (Shandong Riko Chemical Co., Ltd.): 10 parts by weight;
[0127] Foaming masterbatch: 2 parts by weight;
[0128] The materials were mixed according to the above proportions and extruded by JHZ92 / 188 counter-rotating conical twin-screw extruder. The molding process was as follows: main engine speed 15.0 rPm, feed rate 35.0 rPm, barrel temperature between 245°C and 275°C, confluence core temperature 250°C, flange temperature 250°C, and die head temperature 250°C.
[0129] Table 1
[0130]
[0131]
[0132] According to the scanning electron microscope image of the foamed board prepared from the foaming masterbatch of each embodiment and comparative example ( Figure 1-13 ), combined with Table 1, the results are analyzed as follows:
[0133] In the field of foaming, uneven dispersion of bubbles in foamed boards and too small spacing between bubbles will cause uneven mechanical properties of the boards. In addition, if the foaming density is high, fewer boards can be made with the same amount of plastic material, which is costly; if the foaming density is low, more boards can be made with the same amount of plastic material while meeting the mechanical property requirements, which is beneficial to reducing costs. The average density of the foamed boards prepared by the foaming masterbatch of Examples 1-6 does not exceed 1.0 g / cm 3 The nail holding force and static bending strength meet the requirements of GB / T 17657-2022, and the pores are relatively uniform and dense under electron microscope observation, so the method of the present invention is more advantageous. The foaming masterbatch of the present invention can prepare a PET foam material with low density and fine pores while ensuring that the foaming board has sufficient mechanical properties, and can meet the foaming and anti-shrinkage requirements in the modification process of PET and rPET.
[0134] Compared with Example 1, in Example 1, no endothermic agent is added, and the heat released by the chemical foaming agent causes a local temperature rise. The temperature rise is accompanied by a decrease in melt strength and an increase in thermal degradation. The foamed board has an increased density and decreased mechanical properties due to bubble rupture and hole formation.
[0135] Compared with Example 1, in Comparative Example 2, only an inorganic nucleating agent is added, and the density of the board is high. Since the nucleating effect of the inorganic nucleating agent alone is poor, the spacing between bubbles is large and uneven.
[0136] Compared with Example 1, Comparative Example 3 does not add a chemical foaming agent. Although the mechanical properties are better, the gas generation volume is insufficient, the board density is high, and the spacing between bubbles is large.
[0137] Compared with Example 1, Comparative Example 4 has no granulation, no addition of base resin, no resin wrapping, and the foaming agent decomposes prematurely, resulting in a slightly higher board density and larger bubble spacing.
[0138] Compared with Example 1, Comparative Example 5 does not add lubricant and dispersant, such as Fig.11 As shown, the bubbles are not dispersed evenly.
[0139] Compared with Example 1, the trisodium citrate in Comparative Example 6 is untreated commercial trisodium citrate, which contains bound water, has a 100-mesh sieving rate of less than 15%, and has relatively large particles. Fig.12 As shown, the pores of the board are uneven and have string holes. It is speculated that this is because water easily causes PET to hydrolyze at high temperatures, and the large particles cause uneven dispersion of trisodium citrate.
[0140] Compared with Example 1, in Comparative Example 7, an equal amount of aluminum hydroxide was replaced by sodium bicarbonate, and the pores were larger and the board density was larger.
Claims
1. A foaming masterbatch, characterized in that: The foaming masterbatch comprises the following components: (a) 100.0 parts by weight of base resin; (b) 15.0 to 45.0 parts by weight of a heat absorbent; (c) 10.0 to 35.0 parts by weight of an organic foaming agent; (d) 80 to 120 parts by weight of a nucleating agent; (e) 8.0 to 18.0 parts by weight of lubricating and dispersing agents; Wherein, the nucleating agent is a composite nucleating agent composed of an inorganic nucleating agent, a citrate and an organic nucleating agent.
2. The foaming masterbatch according to claim 1, characterized in that: In the nucleating agent, the weight ratio of the inorganic nucleating agent: the citrate: the organic nucleating agent is (1.5-15.0):(60.0-108.0):(9.0-15.0).
3. The foaming masterbatch according to claim 2, characterized in that: The inorganic nucleating agent is selected from one or more of talc, silicon dioxide, hydrotalcite, zeolite powder, mica powder, and montmorillonite; And / or, the citrate is selected from one or more of trisodium citrate or tripotassium citrate; And / or, the organic nucleating agent is selected from one or more of a rosin-based nucleating agent and an ethylene-methacrylate nucleating agent.
4. The foaming masterbatch according to claim 3, characterized in that: The citrate is a pretreated citrate, and the pretreatment step comprises: grinding and sieving the citrate to be treated to obtain a particle size of less than 150 μm, and then drying.
5. The foaming masterbatch according to any one of claims 1 to 4, characterized in that: The heat absorbent is selected from one or more of magnesium hydroxide and aluminum hydroxide.
6. The foaming masterbatch according to any one of claims 1 to 4, characterized in that: The matrix resin is selected from one or more of polyethylene, ethylene-octene copolymer, ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, and ethylene-methyl methacrylate copolymer.
7. The foaming masterbatch according to any one of claims 1 to 4, characterized in that: The organic foaming agent is selected from one or more of azodicarbonamide and 5-phenyltetrazolyl.
8. The foaming masterbatch according to any one of claims 1 to 4, characterized in that: The lubricant and dispersant is selected from one or more of pentaerythritol stearate, calcium stearate, barium stearate, magnesium stearate, polyethylene wax, oxidized polyethylene wax, refined paraffin wax, and polyethylene glycol.
9. The method for preparing the foaming masterbatch according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) adding 100.0 parts by weight of base resin, 15.0-45.0 parts by weight of heat absorbent, 10.0-35.0 parts by weight of organic foaming agent, 80-120 parts by weight of nucleating agent and 8.0-18.0 parts by weight of lubricant and dispersant into a mixer and mixing; (2) Melting and extruding the mixture obtained in step (1) through a screw extruder, granulating, and obtaining a foaming agent masterbatch material; preferably, the barrel temperature of the screw extruder is between 90 and 110° C., the transition zone temperature is between 90 and 110° C., and the head temperature is between 90 and 105° C.; preferably, the main engine speed of the screw extruder is 10 to 20 rpm; Preferably, pelletizing is performed by an air-cooled die face hot cutting system during pelletizing.
10. Use of the foaming masterbatch according to any one of claims 1 to 8 or the foaming masterbatch prepared by the method according to claim 9 in PET foamed products.
Citation Information
Patent Citations
Micro-foaming master batch for polypropylene and preparation method thereof
CN110734597A
Ionomer composite nucleating agent for PET extrusion foaming as well as preparation method and application of ionomer composite nucleating agent
CN112679921A
Master batch capable of being used for extrusion foaming of polyester and application of master batch
CN113121949A
Nucleating agent master batch for PET (Polyethylene Terephthalate) foaming material, preparation method of nucleating agent master batch and PET foaming material
CN118755190A
Formula and process method for producing PET (polyethylene terephthalate) nucleating master batch suitable for supercritical physical foaming
CN118879043A